Analisa Faktor-Faktor yang Berhubungan dengan Kejadian Infeksi Luka Operasi pada Pasien Post Operasi di RSUD Cengkareng - Supriyatin, Supriyatin; Daeli, Weslei; Hidayatullah, Arif (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Introduction: Surgical site infection (SSI) is an infection that occurs in surgical incision wounds. Surgical site infection is a serious health problem and is still often found in every hospital that has services for patient care and surgery. Handling complications from various efforts developed to control infections include improving operating room ventilation, sterilization methods, partitions, surgical techniques and the availability of prophylactic antibiotics. Objectives: To determine what factors are related to the incidence of surgical site infection in postoperative patients at Cengkareng Hospital. Method: This study is a type of quantitative research with an observational method with a cross-sectional approach. This study used secondary data, namely patient files that underwent surgery at Cengkareng Hospital as many as 380 patient files and primary data using questionnaires. Data analysis used Non-Parametric statistics, namely the Chi Square test. Results: Based on the results, it showed that the relationship between comorbidities, age, nature of surgery, duration of surgery, BMI with the incidence of surgical site infection, obtained a p-value <0.05 (0.000). Conclusion: There is a significant relationship between comorbidities, age, type of surgery, duration of surgery, and BMI with the incidence of surgical site infections.